2014
DOI: 10.1016/j.jip.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of entomopathogens for the management of wireworms (Coleoptera: Elateridae) on spring wheat

Abstract: Wireworms, the larval stage of click beetles (Coleoptera: Elateridae), are serious soil dwelling pests of small grains, corn, sugar beets, and potatoes. Limonius californicus and Hypnoidus bicolor are the predominant wireworm species infesting wheat in Montana, particularly in the 'Golden Triangle' area of north-central Montana. Wireworm populations in field crops are increasing, but currently available insecticides provide only partial control, and no alternative management tools exist. In our study, three en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 30 publications
2
51
0
1
Order By: Relevance
“…Similar observation was recorded in tomato plants treated with M. anisopliae, where treated plants showed significant improvement in height, shoot dry weight, root length, and root dry weight [51]. Improvement in the stand counts and yield of wheat plants treated with B. bassiana was also reported by Reddy et al [54]. The ability of endophytic fungi to induce the production of plant growth regulators is believed to be related to plant growth improvement.…”
Section: Discussionsupporting
confidence: 79%
“…Similar observation was recorded in tomato plants treated with M. anisopliae, where treated plants showed significant improvement in height, shoot dry weight, root length, and root dry weight [51]. Improvement in the stand counts and yield of wheat plants treated with B. bassiana was also reported by Reddy et al [54]. The ability of endophytic fungi to induce the production of plant growth regulators is believed to be related to plant growth improvement.…”
Section: Discussionsupporting
confidence: 79%
“…The ability of M. anisopliae and B. bassiana to cause 100% mortalities with the emergence of fungi mycelia growths and sporulation of conidiophores from the cadavers of C. elaeidis clearly indicated that the entomopathogen strains were pathogenic. This agrees with Reddy et al (2014) and Schapovaloff et al (2014) on the susceptibility of Cerambycid beetle Hedypathes betulimus to B. bassiana and M. anisopliae. Maoye et al, (2014), reported that B. bassiana isolate had strong pathogenic and exhibited great potential for sustainable control of brown planthopper Nilaparavata lugeens.…”
Section: Discussionsupporting
confidence: 88%
“…Fungal pathogenicity is affected by wireworm species (78), wireworm state, and environmental conditions: Mortality of A. obscurus larvae from Metarhizium infection increases with both temperature and biomass and depends on wireworm feeding state (77,161,163). The efficacy of entomopathogenic fungi in controlling wireworms (L. californicus, H. bicolor) also depended on the application method and can be superior to seed insecticidal treatments (117).…”
Section: Fungimentioning
confidence: 99%